Development of air‐assisted dispersive micro‐solid‐phase extraction‐based supramolecular solvent‐mediated Fe3O4@Cu–Fe–LDH for the determination of tramadol in biological samples. (29th May 2019) - Ezoddin, Maryam; Adlnasab, Laleh; Afshari Kaveh, Akram; Karimi, Mohammad Ali; Mahjoob, Behnaz
Abstract: A simple method, air‐assisted dispersive micro‐solid‐phase extraction‐based supramolecular solvent was developed for the preconcentration of tramadol in biological samples prior to gas chromatography–flame ionization detection. A new type of carrier liquid, supramolecular solvent based on a mixture of 1‐dodecanol and tetrahydrofuran was combined with layered double hydroxide coated on a magnetic nanoparticle (Fe3 O4 @SiO2 @Cu–Fe–LDH). The supramolecular solvent was injected into the solution containing Fe3 O4 @SiO2 @Cu–Fe–LDH in order to provide high stability and dispersion of the sorbent without any stabilizer agent. Air assisted was applied to enhance the dispersion of the sorbent and solvent. A number of analytical techniques such as Fourier transform‐infrared spectrometry, field emission scanning electron microscope, energy‐dispersive X‐ray spectroscopy and X‐ray diffraction measurements were applied to assess the surface chemical characteristics of Fe3 O4 @SiO2 @Cu–Fe–LDH nanoparticles. The effects of important parameters on the extraction recovery were also investigated. Under optimized conditions, the limits of detection and quantification were obtained in the range of 0.9–2.4 and 2.7–7.5 μg L −1 with preconcentration factors in the range of 450–472 in biological samples. This method was used for the determination of tramadol in biological samples (plasma, urine and saliva samples) with good recoveries.